Financial inclusion for people with disability: a scoping review - Louise Puli; Natasha Layton; Diane Bell; Abu Zafar Shahriar (Global Health Action)
Background Financial exclusion is a human rights issue affecting health equity. Evidence demonstrates that financial exclusion is exacerbated for people with disability and those in low- to middle-income countries (LMIC). Barriers to financial access include limited demand for services, banking inadequacies in catering to people with disability, and insufficiently accessible information technologies (ICT) and infrastructure. Objectives This scoping review sought to identify barriers to and facilitators of financial inclusion for people with disability in LMIC. As a secondary objective, the study explored the potential of financial education and ICT utilisation as viable strategies for enhancing financial inclusion. Methods This review utilised the Arksey and O’Malley framework and PRISMA Checklist for systematic literature examination and data extraction. The WHO’s Environmental Factors guided the analysis to propose potential interventions and to generate recommendations. Results The review analysed 26 publications from various global regions and fields including finance, business, technology, health and disability policy. It identified consistent financial inclusion barriers for people with disability, resulting in a set of global recommendations across attitudes, environment, technology, services, and policy. Conclusions Recommendations include using ICT, digital innovation and multi-stakeholder collaboration to address the financial barriers experienced by people with disability. These efforts, rooted in social justice, aim to include people with disability in LMIC as valued financial sector participants, promoting health and equity.